Розвиток системи підготовки інженерних кадрів у м. Кіровограді в повоєнний період (1945 – 1962 рр.) - Бондаренко, Л. В.; Коломієць, О. Б.; Bondarenko, L.; Kolomiec, E. (КНТУ, 2012)
У статті розглядаються питання розвитку системи професійної технічної освіти Кіровограда у повоєнний період. In the article the questions of development of the system of trade technical education of Kirovograd are examined in a post-war period.
Development of the system of training of engineerings personnels in Kirovograde in a post-war period (1945 – 1962)
Keywords: машинобудівний технікум; інженерні кадри; технічна освіта; machine-building; engineering shots; technical education